Analysis of Strengthening Environmental Literacy in Science Learning at MI GUPPI Jladri Buayan Kebumen - Khoerunisa, Siti; Muzayanah, Sefiyani; Rizqi, Aena Eka; Rahayu, Sabrina Dewi; Umayyah, Hasna; Kholisoh, Zidni; Fauziah, Siti Holifatul; Arianto, Rahman Thooriq; Fatimah, Siti; Fauziah, Muna; Kartika, Nadia Raifah Nawa (Proceeding International Conference on Religion, Science and Education, 2026)
This study aims to analyze the strengthening of environmental literacy in science learning at the GUPPI Jladri Buayan Elementary School in Kebumen. This study used a qualitative approach with a phenomenological approach. Data collection techniques included interviews, observation, and documentation. Data were analyzed using the interactive analysis model of Miles, Huberman, and Saldana, which includes three stages: data condensation, data presentation, and conclusion drawing or verification. The results indicate that environmental literacy-based science learning can strengthen students’ understanding and awareness of the importance of environmental protection. However, obstacles remain in the process of strengthening environmental literacy, including limited plastic waste processing facilities within the school environment.